In search of quality education: The implementation of iso 9000 quality management standards. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
The quality of higher education institutions (HEIs) has often been a subject of concern by relevant authorities around the world. For example, there have been reports about the closures as well as non compliance of HEIs (Aldrige and Rowley, 1998). These situations have made the authorities and general public wondering if the quality of higher education meets people’s expectations. This is because, like many other industries, higher education also needs quality.